Meningkatkan Kesehatan Lansia Pre-Menapouse Pada Masa Pandemi Covid 19 Di RT 02 Perum Yepupa Kota Pekanbaru - Elmia Kursani; Rara Wita; Gusti Shanti Pratiwi (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
Old age will certainly experienced by someone a long life. There are those who use term old age, elderly. Based on data compiled by COVID-19 Task Force of June 20, 2020, percentage of elderly affected by COVID-19 is 13.8% positive elderly, 11.7% treated 12.5% recovered, and 43,7% died. Although  number of positive patients and treated is not too high for elderly group, number of deaths is the highest compared to other age groups, reaching 43.7%. This service aims to describe and improve the health of pre-menopausal elderly during the Covid-19 pandemic at RT 02 Perum Yepupa Pekanbaru City. The method used in service  to provide counseling and exercise for  elderly in the group of pre-menopausal elderly women in RT 02 Perum Yepupa Pekanbaru. hoped that with this counseling and practice of elderly gymnastics,  level of knowledge of pre-menopausal mothers will increase and make them more concerned about their health conditions.